Stress Coping in Adolescents Who Have Disharmonious Families in Sidoarjo: Mengatasi Stres pada Remaja dari Keluarga Tidak Harmonis di Sidoarjo - Rahman, Rifty Aditya; Paryontri, Ramon Ananda (Indonesian Journal of Education Methods Development, 2023)
This qualitative phenomenological study investigates stress coping mechanisms among adolescents from disharmonious families, addressing their responses to challenging and unforeseen family situations. Through semi-structured interviews with two subjects in Sidoarjo, the study identifies distinct coping aspects: problem-focused strategies encompassing planning, competitive activity suppression, behavioral release, coping restrictions, instrumental support utilization, and emotional-focused strategies involving emotional support utilization, emotional release focus, mental liberation, positive reinterpretation and growth, self-blame, acceptance, rejection, humor, substance use, and religious turn. The research reveals that emotional intelligence, stress levels, and religious maturity serve as influential factors shaping stress coping behaviors. These findings offer valuable insights into the complex dynamics of adolescents navigating difficulties within dysfunctional family environments, emphasizing the role of psychological factors and religious engagement in their coping mechanisms. Highlights: Diverse Coping Strategies: This study unveils a range of coping strategies employed by adolescents in dysfunctional families, including problem-focused and emotional-focused approaches. Influential Factors: The research highlights the significant impact of emotional intelligence, stress levels, and religious maturity on adolescents' ability to cope with stress within disharmonious family settings. Qualitative Insight: Using a phenomenological approach, the study offers qualitative insights into the nuanced experiences and coping mechanisms of adolescents facing challenging situations in dysfunctional family environments. Keywords: Adolescent stress coping, Dysfunctional families, Emotional intelligence, Phenomenological approach, Religious maturity